PENGELOLAAN ARSIP DIGITAL DAN PENEMUAN KEMBALI NASKAH DENGAN CEPAT DI KANTOR DESA CIBADUNG KECAMATAN GUNUNG SINDUR KABUPATEN BOGOR - Ratna Suminar; Desilia Purnama Dewi; Nani Nuraini Sarah (Jurnal Pengabdian Sosial, 2023)
ABSTRACT  Research and community service is one of the tasks of tertiary institutions to provide services to the community covering various fields of life by utilizing, developing and applying science, technology and art as an effort to contribute to the progress of society.The method used in this activity is the Participatory Learning and Action (PLA) approach or the Participatory Learning and Practice Process. PLA is a community empowerment method that consists of a learning process (training, brainstorming, and discussion) on topics such as increasing human resources, growing self-confidence, integrity, and responsibility for tasks and afterwards followed by real actions or activities that are relevant to the community. material presented (Mardikanto and Soebiato, 2012: 203). This service activity is carried out in the form of counseling with assistance related to archiving. Archives that were previously stored conventionally can be transferred to digital archives to make it easier for the Village Staff of the Cibadung Village, Gunung Sindur, Bogor City, to store data for the benefit of the community, in accordance with Law on Archive Management no.43, th. 2009, this community service activity was carried out by lecturers and students as the Academic Community so that its presence in the community provides benefits as a form of Higher Education's Tri Dharma. Moreover, in this era of globalization we are entering the digital era, the role of the world of higher education in advancing national development is something that must be done as a manifestation of the tri dharma of higher education, especially in the form of community service activities. This is based on article 20 of law number 20 of 2003 concerning the National Education System (UU DIKNAS) and based on article 24 of the DIKNAS Law which states that there is autonomy by universities to manage their own institutions as centers for providing higher education in the form of outreach, service to the community, the Tri Dharma of Higher Education itself is the three main sources of institutional income. Pamulang University Academics who do community service and service will always appreciate the involvement of all parties through this activity, especially the office administration study program and it is hoped that the level of quality of knowledge and public awareness can increase in a better direction. Keywords: Digital Archives, Manuscripts